Parallelism in Conscious Experience. - Sokolowski, Robert (Daedalus: Journal of the American Academy of Arts & Sciences)
Discusses the ways parallel processing exists in computers and within the nervous and neurological systems of human beings. Parallel processing as an important theme in computer science; Reference to the two tracks of the perceptual and the imaginary that people live in; Difference between presence and absence to the human condition; Existence of physiological reasons for parallel processing; New possibilities opened in neural sciences and computer hardware and programming; More.